Peningkatan Keaktifan Belajar dan Prestasi Belajar Peserta Didik melalui Media Pembelajaran Papan Aksara dan Flipbook Aksara Jawa Kelas V B SDN Bratan 1 Surakarta - Iqbal Candra Maulana; Nur Laily Puspaningtyas; Siti Fatimah Asa’adah (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2025)
Based on the results of preliminary observations in class V B SD Negeri Bratan 1 Surakarta, it is known that the activeness of students during Javanese language learning is still low. This has an impact on their low learning achievement in the subject. This study aims to improve the activeness and learning achievement of students through the use of learning media Papan Aksara and Javanese Script Flipbook. The type of research used is Classroom Action Research (PTK) which is carried out in three stages, namely pre-cycle, cycle I, and cycle II. The subjects of this study were 27 students of class V B SD Negeri Bratan 1 Surakarta. The data collection techniques used included observation and written tests. The data obtained were then analyzed quantitatively. The results showed that there was an increase in the percentage of students' activeness in three consecutive stages, namely 55.56%, 74.07%, and 92.59%. Students' learning achievement also increased from pre-cycle to cycle II seen from the percentage of 18.52%, 59.26%, 85.19%. Thus, the use of Javanese Script Board and Flipbook media effectively increases the activeness and learning achievement of students and can be an alternative to learning Javanese Script that is interesting and meaningful.